Natural Naphthoquinones with Great Importance in Medicinal Chemistry - de Carvalho da Silva, Fernando; Francisco Ferreira, Vitor (Current Organic Synthesis, 2016)
This review involves the chemistry and biochemistry of lapachol, β-lapachone and lawsone, examples of bioactive natural products that still being under biological evaluation and stimulated several research groups to prepare derivatives and analogues and test them against several anticancer, trypanocidal, antinflammatory, tuberculostatic, and antimalarial targets, as well as other parasitology targets related to important infectious diseases.
Keywords: lawsone